Conjugated Polymers of Intrinsic Microporosity (C‐PIMs). (24th June 2014) - Cheng, Ge; Bonillo, Baltasar; Sprick, Reiner S.; Adams, Dave J.; Hasell, Tom; Cooper, Andrew I.
<x xml:space="preserve">Abstract</x> Conjugated microporous polymers (CMPs) have shown great potential for energy and environmental issues, however, poor solubility and processability of most of these materials limit their applications. Herein, a range of linear conjugated polymers of intrinsic microporosity (C‐PIMs) is reported, combining for the first time the properties of conjugated microporous polymers, such as tunable electronic properties and compositional variation, with those of linear polymers of intrinsic microporosity (PIMs) allowing for solution processability and film formation. These soluble materials have a number of potential applications, for example as components in devices where large, porous interfaces are combined with extended electronic conjugation.